Ideology and International Relations: Russian View. Interview with Academician, Doctor of Historical Sciences, Professor, Director of Center of The Situational Analysis at RAS V.G. Baranovskiy - Nikulin, M.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2017)
Vladimir G. Baranovskiy is one of the leading specialists in the field of international relations in Russia. He was born on December 30, 1950 in Moscow. In 1972 he graduated from the Moscow Institute of World Economy and International Relations of the USSR Ministry of Foreign Affairs. In 1973-1976 he studied at the graduate school of the Institute of World Economy and International Relations (IMEMO) of the USSR Academy of Sciences. Since 1976 he works in the structure of the IMEMO Academy of Sciences of the USSR. In 1982-1988 - Head of the International Security Sector of the IMEMO Academy of Sciences of the USSR. In 1986he defended his doctoral thesis on “The European Community in the System of International Relations”. In 1988-1992 - Head of the Department of Western European Studies, IMEMO USSR Academy of Sciences (IMEMO RAS). In 1992-1998 he was the chief research fellow at IMEMO RAS. In 1992-1996 he led the project at the Stockholm International Peace Research Institute (SIPRI). Since 1998 - deputy director of IMEMO RAS. Since 2005 - Professor of the Department of International Relations and Foreign Policy of the Moscow State Institute of International Relations. Since 2011 - full member of the Russian Academy of Sciences. In his interview, V. G. Baranovsky talks about ethics and morality in international relations, multipolarity and the role of ideology in foreign policy.